Assessing knowledge, attitude, and practice of contraception: a cross- sectional study among patients in a semi-urban tertiary hospital - Agarwal, Mukta; Samanta, Sutapan; Bhusan, Divendu; Anant, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unregulated fertility not only disrupts the health of women and child but also disrupts the economy of society and nation. To gain the knowledge about awareness and contraceptive practices in women living in semi-urban area, a cross-sectional study was conducted over one year to evaluate the awareness, acceptance and prevalence of contraceptive methods and various factors affecting the contraceptive usage. Methods: It was a cross sectional study conducted in outpatient department of obstetrics and gynaecology, in a tertiary medical college hospital. The study constituted 300 subjects. It was an interview based study. Data were collected on age, parity, literacy level, residence, knowledge about various contraception, women practicing contraception and reasons for non-use of contraceptives. Results: A total of 300 women in the age group between 18-45 years were studied. It was observed that most of the women belong to the age group of 25 to 34 years (45.33%). 70% belong to rural population. only 20% were para 2 or less.35.33% of the study population were illiterate and 21.67% had education above secondary level. 290 (96.67%) women were aware of one or multiple methods of contraception however, 126 (42%) women accepted the contraceptive practices. Of 300 women, 94 (31.33%) followed permanent methods of contraception. 66% of the study population had experienced unwanted pregnancy and among them 44% pregnancies were aborted. Number of women practicing contraception was very low, i.e. 42% and the main reason of nonpractice of contraception was family pressure mainly in laws, husband gender bias, physical abuse, etc. Conclusions: It was noted that though knowledge of at least one method of contraception was wide among the women but still actual practice was very low. More programs are required to combat the influence of various factors on contraception usage, and emphasizing on the positive effects of the use of contraception.